2017
DOI: 10.7150/ijbs.21149
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization: A Favorable Postoperative Management to Improve Prognosis of Hepatitis B Virus-associated Intrahepatic Cholangiocarcinoma after Surgical Resection

Abstract: Background: There is no information regarding transarterial chemoembolization (TACE) as a postoperative management after hepatic resection for patients with hepatitis B virus (HBV)-associated intrahepatic cholangiocarcinoma (ICC).Methods: Forty-two patients with pathological confirmation of HBV-associated ICC were enrolled. Prognostic impact of the clinicopathological factors as well as postoperative TACE were evaluated. Computed tomography findings of HBV-associated ICC were assessed.Results: Tumor size of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…TACE is often used to manage ICC in unresectable patients, but more recently, adjuvant TACE has also been administered to reduce ICC recurrence . Previous studies have found that adjuvant TACE can improve ICC patient prognosis following resection, mainly by reducing the rate of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TACE is often used to manage ICC in unresectable patients, but more recently, adjuvant TACE has also been administered to reduce ICC recurrence . Previous studies have found that adjuvant TACE can improve ICC patient prognosis following resection, mainly by reducing the rate of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AT, such as transarterial chemoembolization (TACE), chemotherapy, radiotherapy, and comprehensive treatment, has been conducted prevalently worldwide to improve ICC patient prognosis after radical resection . However, there is still controversy over whether ICC patients can benefit from AT after radical resection .…”
Section: Introductionmentioning
confidence: 99%
“…This approach also extends to their reported good outcome of HBV-associated ICC treated with resection and postoperative chemoembolization. (2) Although this study shows interesting results, it exceeds the scope of our review and as previously discussed, prospective clinical trials comparing this to a more definitive treatment option such as LT would better assess the best approach for this patient population.…”
mentioning
confidence: 71%
“…CCA is a rapidly growing and lethal cancer that is usually incurable unless the primary tumor and any metastases are removed completely by surgery (22). As surgical treatment is prone to complications and seriously affects the quality of life of patients, in the postoperative period, it is necessary to strengthen the rehabilitation of patients with CCA from psychological and dietary perspectives (23,24). Following CCA surgery, patients should follow their doctor's advice and (25).…”
Section: Discussionmentioning
confidence: 99%